Cosmic ray observations with the Square Kilometre Array - Buitink, S.; Bouma, Sjoerd; Bray, J.; Corstanje, A.; Desmet, M.; Falcke, H.; Hare, B. M.; Hörandel, J. R.; Huege, T.; James, C. W.; Karastathis, N.; Laub, Philipp; et al. (Proceedings of Science, 2024)
The low-frequency part of the SKA, to be built in Australia, will have an extremely high antenna density of roughly 60,000 antennas within one square kilometer, and is the perfect site for high-resolution studies of air showers. Individual showers will be observed with thousands of antennas simultaneously. The depth of shower maximum Xmax can be reconstructed with a resolution of 10 g/cm2 using methods currently used by LOFAR and the Pierre Auger Observatory. However, the high-resolution SKA data allows the development of new methods that can reconstruct more features of the longitudinal development of air showers, such as the shower length or double-bump profiles. This allows new constraints on both the mass composition and hadronic shower physics. Here we discuss the status of the SKA cosmic-ray program and simulation studies of its capabilities.
CRIS-Team Scopus Importer:2025-02-04